Checklist Of The Pteridophytes Of Chunkankadai Hillock, Kanniyakumari District, Tamil Nadu, India (International Journal of Food and Nutritional Sciences, 2022)
Pteridophytes, the second largest vascular plant group has significant contribution to the plant diversity. The present study deals with the enumeration of 25 species of ferns and fern-allies from Chunkankadai hillock of Kanniyakumari district, Tamil Nadu, India. The result has been presented in the form of a checklist.Pteridophytes are the transition group of plant between non-tracheophytes and spermatophytes. There are about 12,000 species of pteridophytes (ferns and lycophytes) found in the world (Christenhusz and Byng, 2016) of which about 1200 species are reported from the territory of India (Chandra, 2000). Fraser-Jenkins et al. (2017) consider that ‘altogether there are 1114 indigenous taxa and 43 exotics’ for the Indian subcontinent. In peninsular India the Eastern Ghats and Western Ghats has rich source of Pteridophytes (Manickam and Irudayaraj, 1992, 2003; Mandal et al., 2020). In Kanniyakumari district, some workers have done systematic works in ferns and fern-allies (Sharma et al., 1973; Sukumaran et al., 2009; Jeeva et al., 2012; Alfred et al., 2018; Kumari et al., 2018; Felix and Sukumaran, 2021). Chunkankadai hillock is situated in Kanniyakumari district, Tamil Nadu, India. Even though it is known for it rich diversity no checklist available on the Pteridophyte diversity. With this view in mind the present work was planned and carried out.